The Role of Municipalities and the “New Paradigm” in Safety Public Policies in Brazil: an Analysis of the Process of Shifts in Public Policies - Mariana Kruchin (Oñati Socio-Legal Series)
After the democratic transition in Brazil (1984) public safety has become especially relevant in the country due to high rates of crime and the feeling of insecurity among the population, especially in big cities. In this context, prevention is presented in the last decade in response to the repressive policies that have not prevented the continued growth of violence in the country. Regarding public safety, the Brazilian Constitution stipulates in its art. 144 that public safety is carry out by a set of institutions. The list that follows this statement is composed by different (but only) police forces, which are exclusive responsibility of the government of the provinces. In this scenario, there is a strong demand for active participation of municipalities in public safety policies by scholars and professionals who work with the topic. This debate was developed within the political arena whereas the legal field was delegitimize as the field of productions of new truths. This thesis seeks to understand the meaning of the decentralization of public safety policies in socio-legal terms, i.e. the production of meaning and new legal interpretation through social and political discourse and the relations between a new discourse and the possibilities of new practices. A shift in the discourse have altered in practice the terms of the debate in the field, but it was necessary to investigate whether the changes in the level of discourse, rather than the regulatory system are sufficient to alter the existing political model.